Pharmacological and Behavioral Effects of the Synthetic Cannabinoid AKB48 in Rats - Bilel, Sabrine; Tirri, Micaela; Arfè, Raffaella; Stopponi, Serena; Soverchia, Laura; Ciccocioppo, Roberto; Frisoni, Paolo; Strano-Rossi, Sabina; Miliano, Cristina; De-Giorgio, Fabio; Serpelloni, Giovanni; Fantinati, Anna; et al. (Frontiers in Neuroscience, 2019)
AKB48 is a synthetic cannabinoid belonging to a structural class with an indazole core structure, illegally marketed as incense, herbal preparations, or research chemicals for their psychoactive cannabis-like effects. In the present study, we investigated the in vivo pharmacological and behavioural effects of AKB48 in male rats and measured the pharmacodynamic effects of AKB48 and simultaneously determined its plasma pharmacokinetic. AKB48 at low doses preferentially stimulated dopamine release in the nucleus accumbens shell (0.25 mg/kg) and impaired visual sensorimotor responses (0.3 mg/kg) without affecting acoustic and tactile reflexes, which are reduced only to the highest dose tested (3 mg/kg). Increasing doses (0.5 mg/kg) of AKB48 impaired place preference and induced hypolocomotion in rats. At the highest dose (3 mg/kg), AKB48 induced hypothermia, analgesia, and catalepsy; inhibited the startle/pre-pulse inhibition test; and caused cardiorespiratory changes characterized by bradycardia and mild bradipnea and SpO2 reduction. All behavioural and neurochemical effects were fully prevented by the selective CB1 receptor antagonist/inverse agonist AM251. AKB48 plasma concentrations rose linearly with increasing dose and were correlated with changes in the somatosensory, hypothermic, analgesic, and cataleptic responses in rats. For the first time, this study shows the pharmacological and behavioural effects of AKB48 in rats, correlating them to the plasma levels of the synthetic cannabinoid.